Potential Value of Radiomics in the Identification of Stage T3 and T4a Esophagogastric Junction Adenocarcinoma Based on Contrast-Enhanced CT Images - Chang, Xu; Guo, Xing; Li, Xiaole; Han, Xiaowei; Li, Xiaoxiao; Liu, Xiaoyan; Ren, Jialiang (Frontiers in Oncology, 2021)
Purpose: This study was designed to evaluate the predictive performance of contrast-enhanced CT-based radiomic features for personalized differential diagnosis of esophagogastric junction(EGJ) adenocarcinoma at stages T3 and T4a. Methods: Two-hundred patients with 44 T3 and 156 T4a EGJ adenocarcinoma lesions were enrolled in this study. Traditional CT features were obtained from contrast-enhanced CT images, and the traditional modal was constructed by multivariate logistic regression. A radiomics model was established based on radiomics features from venous CT images, and the radiomics score (Radscore) of each patient was calculated. A combined nomogram diagnostic model was constructed based on Radscores and traditional features. The diagnostic performances of these three models (traditional model, radiomics model and nomogram) were assessed with receiver operating characteristics curves. Sensitivity, specificity, accuracy, positive predictive value, negative predictive value, and areas under curves (AUC) of models were calculated, with which the performances of models were evaluated and compared with each other. Finally, the clinical effectiveness of the three models was evaluated by decision curve analysis (DCA). Results: An eleven-feature combined radiomics signature and two traditional CT features were constructed as the radiomics and traditional features models, respectively. The Radscore was significantly different between EGJ adenocarcinoma cases at stages T3 and T4a. The combined nomogram performed the best and has potential clinical usefulness. Conclusion: The developed combined nomogram could be useful in differentiating T3 and T4a stages in EGJ adenocarcinoma and may facilitate the treatment decision-making process of T3 and T4a EGJ adenocarcinoma.